Clear Cell Papillary Renal Cell Carcinoma Incidentally Discovered in a Patient With Normal Renal Function: A Case Report - Toru Inoue; Masahiro Fuse; Satoki Abe; Shinya Sejiyama; Kazuhiro Kawamura; Yuzo Oyama; Tadasuke Ando; Toshitaka Shin (IJU Case Reports, 2025)
ABSTRACT Introduction Clear cell papillary renal cell carcinoma is a distinct histopathological entity first characterized in patients with end‐stage renal disease. Although increasingly reported in patients with normal renal function, it remains relatively unfamiliar in routine clinical practice. Case Presentation A 75‐year‐old male with normal renal function presented with an incidentally discovered left renal mass. Radiological evaluation revealed a mass with a distinct enhancement pattern. Considering the patient's preference for surgical management, robot‐assisted partial nephrectomy was performed, confirming clear cell papillary renal cell carcinoma, with immunohistochemistry demonstrating diffuse cytokeratin 7‐positivity, alpha‐methylacyl‐CoA racemase‐negativity, and cup‐shaped carbonic anhydrase IX staining. Conclusion This case demonstrated the characteristic features of clear cell papillary renal cell carcinoma in a patient with normal renal function. Nephron‐sparing surgery and rigorous follow‐up protocols are crucial management strategies. Future studies with larger cohorts are needed to define the natural history and optimal management of clear cell papillary renal cell carcinoma.